Efektivitas Metode Demonstrasi Terhadap Keterampilan Siswa Dalam Memandikan Jenazah Pada Mata Pelajaran Fiqih - Fauziah, Hapsah; Jayagiri, Indra (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
Islamic Religious Education has an important role, including in terms of social elements. One of the materials in Islamic Religious Education that contains social values ​​and demands emphasis on aspects of affection and practice is taking care of corpses, which is a worship material in the Fiqh subject. In this material, each student is required to be able and skilled to practice it. The method is one of the ways used by teachers so that students can understand and even practice the material presented. One method that is suitable for delivering material on taking care of corpses is the demonstration method. This is the background for researchers to conduct this research. The objectives of this study are to describe; 1) students' skills in bathing corpses in the Fiqh subject of class IX MTs. Al-Musaddadiyah Garut; 2) the effectiveness of the demonstration method in bathing the corpse in the Fiqh subject of class IX MTs. Al-Musaddadiyah Garut; and 3) the effectiveness of the demonstration method on students' skills in bathing the corpse in the Fiqh subject of class IX MTs. Al-Musaddadiyah Garut. This study uses a qualitative research method with a descriptive approach. The data collection techniques used are interviews, observation, and documentation. While the analysis technique used in this study is a descriptive analysis technique consisting of three flows, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that; 1) student skills in bathing corpses in class ix MTs.Al-Musaddadiyah scratch can be said to be successful, see 80% of students can carry out the practice test of fiqih learning especially on the sub-chapter of bathing corpses have met the minimum requirement criteria (KKM); 2) implementation of learning by using demonstration methods on fiqih subjects in particular on the sub-chapter bathing corpses is effective. And then;  3) the demonstration method is said to be effective in improving student body bath skills on fiqih subjects di MTs.Al-Musadadiyah Garut, because students not only understand but also are skilled at bathing bodies.  Keyword: Islamic Education, Demonstration Method, Body Bath Skills.